2016
DOI: 10.1080/02726351.2016.1196276
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of 6061 aluminum alloy reinforced with Si3N4/n-Gr and its wear performance optimization using integrated RSM-GA

Abstract: In this research work the dry sliding wear behavior of a hybrid aluminum metal matrix composite is evaluated. Al 6061 is used as a matrix material while Si3N4 and nano-graphite powder (3-15 wt.%) are used as reinforcements. These two reinforcements (50 wt.% of each) were blended in high energy ball mill for homogeneous mixing to get the sound aluminum matrix composite (AMC). The hybrid composite is made by stir casting route and its wear rate was investigated against an EN32 steel disc surface, using a pin-on-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…This decrease in wear was associated with the higher microhardness as the reinforcement content increased. An increase in hardness in the composites expectedly lowered the material removal rate in the composites, and thereby reduced the wear [30]. However, this trend was found to be relatively small when compared with those of other factors.…”
Section: Effect Of Variables On Wear Behaviourmentioning
confidence: 93%
“…This decrease in wear was associated with the higher microhardness as the reinforcement content increased. An increase in hardness in the composites expectedly lowered the material removal rate in the composites, and thereby reduced the wear [30]. However, this trend was found to be relatively small when compared with those of other factors.…”
Section: Effect Of Variables On Wear Behaviourmentioning
confidence: 93%
“…Graphite affords lubrication fallout and dwindle the friction and wear in the course of sliding. But a larger content of Gr can manage more advanced wear rate by virtue of the devaluation in fracture strength of AMCs [15]. Graphite also improves the dimensional stability.…”
Section: Methodsmentioning
confidence: 99%
“…4(f)-(g) shows rich interfaces between matrix and reinforcement. Microstructure images by Sharma et al [50] reported that, there were a uniform dispersion of Si3N4 and nano graphite particles in AA6061 alloy while the composite is fabricated via stir casting route. Amigo et al [51]…”
Section: A Physical Properties : Density and Porositymentioning
confidence: 99%